Preparation of Two Novel Schiff Base Polymers and Their Eu(III)/Yb(III) Complexes. Issue 1 (21st December 2018) - Zhang, Dingjun; Huo, Caixia; He, Ling; Lu, Wenjiang; Feng, Zhaoxuan
Abstract : Novel Schiff Base photosensitive polymers, with coordination property, were synthesized via the condensation reaction. Using them as macromolecular ligands, a series of polymer rare earth complexes were prepared via the coordination reaction. The structure of the polymers and their corresponding complexes were examined by FT–IR and UV spectroscopy; the fluorescence properties of the complex were mainly investigated by fluorescence spectrum, and thermal properties were investigated by DSC and TGA. The luminescence properties of the Eu(III)/Yb(III) complex in dimethyl formamide solutions were investigated. The results indicate that they are promising in the field of light–emitting materials and can be further mixed with suitable polymers to form functional rare earth polymers.